2009
DOI: 10.21273/hortsci.44.6.1672
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture of ‘Myrobalan’ (Prunus cerasifera Ehrh.) Embryos

Abstract: In vitro embryo culturing has arisen as a powerful tool for embryo germination of low-viability seeds. This tool has been used to germinate seeds of early-maturing or hybrid Prunus species. ‘Myrobalan’ (Prunus cerasifera Ehrh.) is a widely used rootstock for plum and apricot cultivars and its interspecific hybrids have a clear potential for breeding purposes. However, early seed abortion is often a problem in interspecific crosses because no protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Sources indicate that there are likely germination inhibitors present in the cotyledon and testa in Prunus and simply removing testa increased in vitro seed germination of peach by 10% (S xan and Yildirim, 2009). Arbeloa et al (2009) reported 60% higher germination of Prunus cerasifera 'Myrobalan' embryos 6.5-10 mm long compared with embryos that were 0.5-2 mm, which indicates that regardless of our seed treatment the germination likely would have remained modest in the 6 and 9 WAP collections. Although shoot emergence at 12 WAP with cold stratification was higher than the groups in Expt.…”
Section: Resultsmentioning
confidence: 90%
“…Sources indicate that there are likely germination inhibitors present in the cotyledon and testa in Prunus and simply removing testa increased in vitro seed germination of peach by 10% (S xan and Yildirim, 2009). Arbeloa et al (2009) reported 60% higher germination of Prunus cerasifera 'Myrobalan' embryos 6.5-10 mm long compared with embryos that were 0.5-2 mm, which indicates that regardless of our seed treatment the germination likely would have remained modest in the 6 and 9 WAP collections. Although shoot emergence at 12 WAP with cold stratification was higher than the groups in Expt.…”
Section: Resultsmentioning
confidence: 90%
“…However, seeds of temperate fruit species require a long time to germinate under traditional stratification or natural conditions. Therefore, fast and uniform germination techniques are desirable for fruit-growing and breeding studies [14]. Various methods have been tried to overcome dormancy of stone fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse concentrations of plant growth regulators (PGRs) and mineral elements affect the in vitro propagation of clonal rootstock. There are limited in vitro studies on the micropropagation of Myrobalan 29C rootstocks (Arbeloa et al, 2009;Akşehirli, 2010;Movsiuw, 2011;Plopa et al, 2012;Özbek et al, 2014;Shabani et al, 2015;Nasri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%